Prevalence and risk factors of hepatitis C and B virus infections in hemodialysis patients and their spouses: A multicenter study in Beijing, China1. Issue 3 (22nd January 2013) - Su, Yingying; Yan, Ruixue; Duan, Zhongping; Norris, Jessie L.; Wang, Lu; Jiang, Yan; Xing, Wenge; Chen, Yu; Xiao, Yao; Li, Lu; Tao, Jun; Wang, Ning
Abstract Hemodialysis patients are at risk for hepatitis C and B virus infections. This study investigated the prevalences and risk factors of HCV and HBV infection and the distribution of HCV genotypes among hemodialysis patients and their spouses. From August to November 2011, a cross‐sectional study was conducted on 20 hemodialysis units in Beijing to investigate prevalences and risk factors for markers of HCV and HBV among 2, 120 patients and 409 spouses. In hemodialysis patients, prevalences of anti‐HCV, HCV RNA, and hepatitis B surface antigen (HBsAg) were 6.1%, 4.6%, and 7.0%, respectively. The prevalence of HCV antibodies among spouses was 0.5%, of HCV RNA was 0.2%, and of HBsAg was 4.2%. Risk factors for HCV infection were dialysis duration, blood transfusion, and attending more than one dialysis unit. HBV infection was independently associated with age, family member with hepatitis infection, gender, and surgery. The predominant HCV genotypes were 1b (89.0%) and 2a (7.7%), and genotypes 3a, 3b, and 6a were each 1.1%. A significant decrease in HCV and HBV prevalences in Chinese dialysis units showed that infection control measures were effective. However, because nosocomial transmissions persist, strict adherence to infection control measures should be emphasized to reduce the risk of transmission. J. Med. Virol. 85:425–432, 2013. © 2013 Wiley Periodicals, Inc.